Assertive and Directive Illocutionary Acts and Politeness Strategies in Reacher Season 1: A Pragmatic Analysis - Yohanes Darrel Tumbur Pardomuan; Devi Hellystia (Journal of linguistics, culture and communication, 2026)
This study investigates how authority and dominance are linguistically constructed through illocutionary acts in Reacher Season 1. Focusing exclusively on the main character’s utterances, the research examines the use of Assertive and Directive speech acts alongside politeness strategies in high-pressure contexts such as interrogations, threats, and negotiations. Employing a descriptive qualitative approach grounded in Searle’s classification of illocutionary acts and Brown and Levinson’s politeness framework, the study analyzes 252 utterances extracted from the official subtitles of all eight episodes. The findings reveal a clear dominance of Assertive acts (183 occurrences) over Directives (69 occurrences), indicating that Reacher primarily exerts authority by controlling information rather than by issuing commands. Informing and Stating emerge as the most frequent subtypes, reinforcing his role as a strategist who shapes events through reasoning and factual control. Although Directives appear less frequently, Commanding functions as a decisive tool in urgent situations. Across both categories, Bald on Record strategy overwhelmingly dominates, reflecting efficiency and urgency in high-stakes interactions. However, the selective use of Positive and Negative Politeness demonstrates situational adaptability. The study argues that Reacher’s authority is constructed not merely through overt dominance but through calculated communicative choices that balance assertiveness, efficiency, and contextual sensitivity.